2006
DOI: 10.1177/0361198106197400116
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Pavement Testing to Compare Efficiency of Overlay Materials Used in Brazil

Abstract: In Brazil, asphalt rubber (AR) has been used to delay reflection cracking in overlays since the 1990s. To quantify reflection cracking evolution in AR and asphalt concrete (AC) overlays, an accelerated pavement testing (APT) study was carried out by the Federal University of Rio Grande do Sul and the State Roads Department. Overlays 5.0-cm thick were set on sections with identical structures (severely cracked AC wearing course and granular base), and from March 2003 to February 2005 a traffic simulator applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The accelerated pavement testing (APT) technique emerges as the research requires, which aims to apply continuous wheel loads on full-scale test sections under controlled load and environmental conditions, until the structure fails within a short period of time [ 15 , 16 ]. Researchers from Australia [ 17 ], South Africa [ 18 ], the United States [ 19 ], France [ 20 ], Brazil [ 21 ], Costa Rica [ 22 ], and so on, have contributed a lot to the field over the last decades. Research results can be found in the long-term performance evaluations [ 23 , 24 , 25 , 26 ] and distress mechanism investigations [ 27 , 28 ] of pavement materials and structures, based on the APT technique, whereas there are lacking studies on the calibration methods of rut prediction models under complex test conditions, based on APT.…”
Section: Introductionmentioning
confidence: 99%
“…The accelerated pavement testing (APT) technique emerges as the research requires, which aims to apply continuous wheel loads on full-scale test sections under controlled load and environmental conditions, until the structure fails within a short period of time [ 15 , 16 ]. Researchers from Australia [ 17 ], South Africa [ 18 ], the United States [ 19 ], France [ 20 ], Brazil [ 21 ], Costa Rica [ 22 ], and so on, have contributed a lot to the field over the last decades. Research results can be found in the long-term performance evaluations [ 23 , 24 , 25 , 26 ] and distress mechanism investigations [ 27 , 28 ] of pavement materials and structures, based on the APT technique, whereas there are lacking studies on the calibration methods of rut prediction models under complex test conditions, based on APT.…”
Section: Introductionmentioning
confidence: 99%